Relationships between pig birth weight and expression of the immediate early gene EGR-1 in umbilical cord Wharton's jelly - Morton, J. M.; Rathbun, Theresa J.; Davis, Duane L. (My University, 2016)
In humans the expression of EGR-1 in umbilical cord Wharton’s jelly has been related to birth weight. In umbilical cords of small for gestational age (SGA) babies the expression of EGR-1 is increased compared to normal weight contemporaries. Expression of EGR-1 appears to indicate prenatal programming resulting from growth restriction. It is known that SGA babies develop slower compared to normal sized babies and in many ways are comparable to small birth weight pigs. Therefore we investigated whether EGR-1 expression in pig umbilical cord Wharton’s jelly is related to birth and weaning weights. Fifty-seven umbilical cords were collected from 5 litters (PIC; 326 × 1050), along with birth and weaning weights. Wharton’s jelly tissue was snap frozen and stored (?80°C) until RNA was extracted (Trizol method), RNA quantity determined using the Nanodrop method and quality was evaluated with an Agilent Bioanalyzer. Quantitative PCR was used to determine expression of EGR-1 compared to 18S and the data converted to relative expression using RNA from newborn pig testis as a calibrator. Birth weight (P < 0.003) and wean weight at d 21 (P < 0.026) were correlated negatively with EGR-1 expression. Larger pigs had decreased expression of EGR-1 compared to smaller pigs. The umbilical cords from the 14 pigs with the lowest expression of EGR-1 (bottom quartile) included only one pig with a birth weight < 1.11 kg while the top quartile included 9 pigs weighing less than 1.11 kg at birth (P < 0.002, chi square). In response to rising global demands for pork, swine producers have increased litter sizes and this has resulted in more small pigs at birth. We have identified that pigs with a birth weight below 1.11 kg have increased mortality rates by weaning age (3–4 wk). These pigs do not grow as well as their heavier contemporaries and result in lower value carcasses. Expression of EGR-1 in umbilical cords of low birth weight pigs appears to reflect prenatal programming comparable to that identified in SGA babies.
Citation: Morton, J. M., Rathbun, T., & Davis, D. L. (2016). Relationships between pig birth weight and expression of the immediate early gene EGR-1 in umbilical cord Wharton's jelly. Journal of Animal Science, 94, 149-149. doi:10.2527/msasas2016-317
Keywords: Pigs; Prenatal Programming; Egr-1; Agriculture